ZAANGAŻOWANIA KOŚCIOŁA KATOLICKIEGO NA RZECZ MIGRANTÓW – PRZESŁANKI DOKTRYNALNO-PRAWNE - Wojnicz, Piotr (Civitas et Lex, 2017)
The Catholic Church is naturally associated with migrants and its history and doctrine are inextricably linked with the migration of people. Many of the documents of the Catholic Church refer to the history of human migration. The responsibility of the Catholic Church for migrants has deep historical and theological roots. The Catholic Church sees both the positive and the negative sides of this phenomenon The pastoral care of migrants is a response to the needs of these people. It does not replace the territorial structures. They both work closely together and complement each other. The primary objective of the pastoral care of migrants is to enable migrants to integrate with the local community. An important element of these structures are religious orders of men and women. The most important thing for migrants is the Christian attitude of the local community to them. Church repeatedly stressed the importance of hospitality to migrants. Both human and Christian attitude towards migrants expresses itself in a good reception, which is the main factor in overcoming the inevitable difficulties, preventing opposites and solving various problems. This attitude helps to alleviate the problems associated with the process of social integration.